Stenotrophomonas rhizophila Ep2.2 inhibits growth of Botrytis cinerea through the emission of volatile organic compounds, restricts leaf infection and primes defense genes - Raio, Aida; Brilli, Federico; Neri, Luisa; Baraldi, Rita; Orlando, Francesca; Pugliesi, Claudio; Chen, Xiaoyulong; Baccelli, Ivan (Frontiers in Plant Science, 2023)
The bacterium Stenotrophomonas rhizophila is known to be beneficial for plants and has been frequently isolated from the rhizosphere of crops. In the present work, we isolated from the phyllosphere of an ornamental plant an epiphytic strain of S. rhizophila that we named Ep2.2 and investigated its possible application in crop protection. Compared to S. maltophilia LMG 958, a wellknown plant beneficial species which behaves as opportunistic human pathogen, S. rhizophila Ep2.2 showed distinctive features, such as different motility, a generally reduced capacity to use carbon sources, a greater sensitivity to fusidic acid and potassium tellurite, and the inability to grow at the human body temperature. S. rhizophila Ep2.2 was able to inhibit in vitro growth of the plant pathogenic fungi Alternaria alternata and Botrytis cinerea through the emission of volatile compounds. Simultaneous PTR-MS and GC-MS analyses revealed the emission, by S. rhizophila Ep2.2, of volatile organic compounds (VOCs) with well-documented antifungal activity, such as furans, sulphur-containing compounds and terpenes. When sprayed on tomato leaves and plants, S. rhizophila Ep2.2 was able to restrict B. cinerea infection and to prime the expression of Pti5, GluA and PR1 plant defense genes.